Expenditure in R&D and local development - an analysis of Italian provinces - Michele Capriati (European Regional Science Association (ERSA), 2005)
The expenditure capacity in R&D is regarded as an important factor for the growth of modern economies. However, even more important is to understand the interaction between research resources and the single territories together with their concrete impact on innovation processes. In fact it is at the local level that the innovation dynamics based on implicit knowledge are generated and disseminated. In order to analyse these processes the present level of aggregation of R&D expenditure data is limited to administrative regions and is still high, this reducing the ability to carry out more precise investigations. The present paper makes an estimate of R&D expenditure for different institutional categories in Italian municipalities (University, Public Administration, and Business). The estimated database has been completed with economic variables referring to the individual municipalities. This has enabled us to carry out a correlation and a cluster analysis and identify groups of municipalities with different characteristics concerning innovation and local development.
Keywords: 330